1996
DOI: 10.1007/bf02265257
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive early prenatal molecular diagnosis using retrieved transcervical trophoblast cells

Abstract: Fetal DNA was recovered from 17 of 39 (44%) transcervical cell (TCC) samples obtained between 7 and 9 weeks of gestation by endocervical canal flushing. Trophoblast retrieval was adequate for polymerase chain reaction (PCR) amplification of Y chromosome-specific DNA sequences and detection of paternal-specific microsatellite alleles. The fetal sex predicted by PCR in TCCs was confirmed in all cases by karyotype analysis of chorionic villi at 10 weeks of gestation. The absence of the disease-associated paternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…These studies, as well as those carried out by other investigators (Kawamura et al 1995;Massari et al 1996;BahadoSingh et al 1995;Briggs et al 1995;Ishai et al 1995;Maggi et al 1996;Daryani et al 1997) were all performed on small numbers of samples collected at about 10-12 weeks of gestation, just before termination of pregnancy. The presence of cells from male fetuses was documented using FISH, conventional PCR, or quantitative fluorescent PCR (QF- (Pertl et al 1994;Sherlock et al 1997a,c) with DNA markers specific for chromosome Y.…”
Section: Frequencies Of Fetal Cells In Tcc Samplesmentioning
confidence: 99%
“…These studies, as well as those carried out by other investigators (Kawamura et al 1995;Massari et al 1996;BahadoSingh et al 1995;Briggs et al 1995;Ishai et al 1995;Maggi et al 1996;Daryani et al 1997) were all performed on small numbers of samples collected at about 10-12 weeks of gestation, just before termination of pregnancy. The presence of cells from male fetuses was documented using FISH, conventional PCR, or quantitative fluorescent PCR (QF- (Pertl et al 1994;Sherlock et al 1997a,c) with DNA markers specific for chromosome Y.…”
Section: Frequencies Of Fetal Cells In Tcc Samplesmentioning
confidence: 99%
“…e results of this study on the one hand con�rm that IUL samples are a valuable source of trophoblastic cells that can be easily isolated [10] and on the other hand suggest that aneuploidies such as trisomy 21 and monosomy X, that account for a remarkable proportion of all clinically relevant chromosomal disorders, can accurately be detected in these cells by a QF-PCR assay. Our results are important, as, in spite of the body of research on TCCs, very little had been previously reported on the detection of chromosomal or genetic disorders using these cells [15][16][17][18][19], which is no doubt a crucial point in view of the possible clinical use of the procedure.…”
Section: Discussionmentioning
confidence: 86%
“…), provided that fetal clones are identified first by detection of paternal specific microsatellite alleles (Massari et al, 1996) or dinucleotide repeat polymorphisms. The data recorded further imply that between 100 and 1000 fetal cells, approximately, are available for interphase cytogenetic diagnosis, a figure more than sufficient for routine clinical application, considering that immunocytochemical staining for y-globin can identify fetal nucleated red cells (Zheng et al, 1993(Zheng et al, , 1999, thus making a selective FISH analysis possible.…”
Section: Discussionmentioning
confidence: 99%